Transformasi Pendidikan: Analisis Model Sekolah Penggerak dalam Meningkatkan Kualitas Pembelajaran di SMP Telkom Maakassar: Educational Transformation: Analysis of the Driving School Model in Improving the Quality of Learning at SMP Telkom Maakassar - AuliaIrfan; Andira Apriliyanti Amri; Fadel Rezki Adhari Mansyur; Muhammad Zainal Arifin; Arismundar; Ahlun Ansar (Al-Gafari : Manajemen dan Pendidikan, 2025)
To improve the quality of learning in Indonesia, especially at the junior high school (SMP) level, educational transformation is an important process. The "Activator School" is one model used to achieve this goal. This program aims to improve the quality of learning through strengthening the curriculum, increasing teacher capabilities, and using technology in the learning process. In an effort to improve the quality of learning, this research investigates the implementation of the Driving School model at Telkom Makassar Middle School. To collect data, a qualitative approach with descriptive analysis was used. Observations, interviews and documentation are also used. The research results show that the implementation of the Driving School model at Telkom Makassar Middle School has improved the quality of learning, especially in terms of technology-based learning, increasing teacher capabilities, and increasing student participation. Despite this, there are still problems implementing it. These include limited resources and facilities, as well as the need for ongoing training for teachers. In short, the Driving School model at Telkom Makassar Middle School can be considered an example of success in educational transformation that focuses on improving the quality of learning.